HeKatE Rule Design Methodology Overview - Ligęza, Antoni; Nalepa, Grzegorz J. (Przegląd metodologii projektowania systemów regułowych HeKatE, 2010)
This paper presents a methodology and tools for design and development of rulebased systems. Efficient knowledge representation is based on the Extended Tabular Trees -XTT2 formalism. The design process is a top-down one. A conceptual model is developed with the ARD+ diagrams representing functional dependencies among attributes. On the basis of ARD+ a scheme of the XTT2 rule-based model is generated and filled with knowledge. A set of tools supporting design and verification is described and design methodology is outlined.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 58-68
Keywords: rule-based systems; design and development of rule-based systems